Central Coherence in Full Recovery of Anorexia Nervosa. (21st November 2012) - Lindner, Susanne E.; Fichter, Manfred M.; Quadflieg, Norbert
Abstract Objective This study examined central coherence as a possible endophenotype in a large sample of women recovered from anorexia nervosa (rec AN). Recovery was defined by considering physiological, behavioural and psychological variables. Method A total of 100 rec AN women and 100 healthy women completed the Rey Complex Figure Test, a measure for visual–spatial central coherence. The participants were matched 1:1 for age and educational level. Results Compared with the healthy control group, the rec AN group showed better accuracy in the copy condition. There was a trend for a local strategy in the rec AN group compared with a global strategy in the healthy control group. Conclusions This sample of rec AN women showed no inefficiencies in global processing but a superior local processing after full recovery from AN. Copyright © 2012 John Wiley & Sons, Ltd and Eating Disorders Association.